Myostatin Promotes Interleukin-1β Expression in Rheumatoid Arthritis Synovial Fibroblasts through Inhibition of miR-21-5p - Hu, Sung-Lin; Chang, An-Chen; Huang, Chien-Chung; Tsai, Chun-Hao; Lin, Cheng-Chieh; Tang, Chih-Hsin (Frontiers in Immunology, 2017)
Rheumatoid arthritis (RA) is characterized by the infiltration of a number of pro-inflammatory cytokines into synovial fluid and patients with RA often develop joint destruction and deficits in muscle mass. The growth factor myostatin is a key regulator linking muscle mass and bone structure. We sought to determine whether myostatin regulates rheumatoid synovial fibroblast activity and inflammation in RA. We found that levels of myostatin and interleukin (IL)-1β (a key pro-inflammatory cytokine in RA) in synovial fluid from RA patients were over-expressed and positively correlated. In in vitro investigations, we found that myostatin dose-dependently regulated IL-1β expression through the ERK, JNK and AP-1 signal-transduction pathways. Computational analysis confirmed that miR-21-5p directly targets the expression of the 3’ untranslated region (3'UTR) of IL-1β. Treatment of cells with myostatin inhibited miR-21-5p expression and miR-21-5p mimic prevented myostatin-induced enhancement of IL-1β expression, showing an inverse correlation between miR-21-5p and IL-1β expression during myostatin treatment. We also found significantly increased paw swelling in an animal model of collagen-induced arthritis (CIA), compared with controls; immunohistochemistry staining revealed substantially higher levels of myostatin and IL-1β expression in CIA tissue. Our evidence indicates that myostatin regulates IL-1β production. Thus, targeting myostatin may represent a potential therapeutic target for RA.